2007
DOI: 10.2353/ajpath.2007.060806
|View full text |Cite
|
Sign up to set email alerts
|

Aggregated Myocilin Induces Russell Bodies and Causes Apoptosis

Abstract: Primary open-angle glaucoma with elevated intraocular pressure is a leading cause of blindness worldwide. Mutations of myocilin are known to play a critical role in the manifestation of the disease. Misfolded mutant myocilin forms secretion-incompetent intracellular aggregates. The block of myocilin secretion was proposed to alter the extracellular matrix environment of the trabecular meshwork, with subsequent impediment of aqueous humor outflow leading to elevated intraocular pressure. However, the molecular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
51
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(55 citation statements)
references
References 74 publications
3
51
0
1
Order By: Relevance
“…Initially, to assess for potential differences in how eGLuc2-tagged MYOC is secreted and handled within the cell, we compared the secretion and intracellular profile of untagged WT MYOC and WT MYOC FLAG (FT, used extensively in past experiments 2,37,38 ) to WT MYOC eGLuc2. We found that indeed, all three variants are readily secreted from transfected cells and detectable in the media 48 hours after initial transfection (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Initially, to assess for potential differences in how eGLuc2-tagged MYOC is secreted and handled within the cell, we compared the secretion and intracellular profile of untagged WT MYOC and WT MYOC FLAG (FT, used extensively in past experiments 2,37,38 ) to WT MYOC eGLuc2. We found that indeed, all three variants are readily secreted from transfected cells and detectable in the media 48 hours after initial transfection (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Impaired degradation 74 of myocilin aggregates presumably leads to aberrant accumulation in other relevant cellular compartments 9; 13; 14; 75; 76; 77; 78 , affecting protein folding and other cellular processes more generally. Under these conditions, even degradation by autophagy 79 , which, in the case of mutant myocilin may be assisted by peroxisomes 8 , likely cannot compensate sufficiently for ERAD inhibition, leading to apoptosis 9; 13; 14 . Once TM cells die, it is straightforward to foresee that cellular debris would be detrimental to TM function and proper outflow, leading to IOP elevation.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies note intracellular sequestration of mutant myocilin 8; 9; 10; 11 . Some studies further report an endoplasmic reticulum (ER) stress response 12; 13 , including explicit colocalization of large juxtanuclear myocilin aggregates with known ER chaperones 9; 14 leading to apoptosis and cell death 9; 13; 14 . The majority of myocilin variants examined, located in the ~30 kDa myocilin C-terminal olfactomedin domain (myoc-OLF) 5 , thermally destabilize the domain but in vitro retain secondary structure similar to wild-type (WT); age of diagnosis follows the extent of destabilization of myoc-OLF 15 .…”
Section: Introductionmentioning
confidence: 99%
“…Several in vitro studies demonstrated that disease-causing MYOC mutants are secretion incompetent and accumulate in the endoplasmic reticulum (ER), inducing ER stress. 2432 Using Tg-MYOC Y437H mice expressing mutant human myocilin, we have shown that ER stress is associated with IOP elevation in MYOC-associated glaucoma. 26 We have recently demonstrated that ER stress is also associated with glucocorticoid-induced ocular hypertension.…”
mentioning
confidence: 99%